Nomenclature and taxonomy of Salix floccosa, S. opsimantha and S. austrotibetica - Li, He; Liao, Shuai; Zhang, Zhixiang (Phytotaxa, 2015)
Salix floccosa Burkill was originally described based on a mixed collection of two different taxa. Chinese authors in many cases identified S. floccosa, although the species should correctly be named S. austrotibetica N. Chao. The name S. floccosa is lectotypified. S. spodiophylla Handel-Mazzetti, S. dolia var. lineariloba N. Chao, S. eriostachya var. lineariloba (N. Chao) G.H. Zhu, S. spodiophylla f. liocarpa K.S. Hao ex C.F. Fang & A.K. Skvortsov and S. spodiophylla var. liocarpa (K.S. Hao ex C.F. Fang & A.K. Skvortsov) G.H. Zhu are recognized as S. floccosa; S. annulifera var. glabra P.Y. Mao & W.Z. Li and S. floccosa (pro parte) are synonymised with S. opsimantha C.K. Schneider; S. floccosa var. leiogyna P.Y. Mao & W.Z. Li is treated as a synonym of S. austrotibetica. Furthermore, the circumscription of S. austrotibetica is emended to include partly downy to densely downy ovary.